2012
DOI: 10.1017/s0022029912000337
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dry period length on reproductive performance and productivity of Lacaune dairy sheep under an intensive management system

Abstract: Intensive management is almost the only way to ensure dairy farm profitability. The dry period length (DPL) is a key factor in the productivity and health of dairy cows, but whether the same is true of dairy sheep is unclear. This study investigated the effects of DPL on the performance of Lacaune sheep under intensive management. We recorded 8136 lactations from 4220 ewes on one farm for the period 2005-2010, and data from a total of 6762 complete lactations 1-4 were included in the study. The length of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 32 publications
4
11
0
Order By: Relevance
“…Our data suggests even higher IgG concentration can be achieved in colostrum if PDP is prolonged beyond 90 d, but this is not advisable for production. Taken together, our results support the conclusion of Hernandez et al (2012) that a 30 d prepartum is the most appropriate drying period for milk production in Lacaune ewes reared under intensive conditions.…”
Section: Resultssupporting
confidence: 92%
“…Our data suggests even higher IgG concentration can be achieved in colostrum if PDP is prolonged beyond 90 d, but this is not advisable for production. Taken together, our results support the conclusion of Hernandez et al (2012) that a 30 d prepartum is the most appropriate drying period for milk production in Lacaune ewes reared under intensive conditions.…”
Section: Resultssupporting
confidence: 92%
“…However, it should be noted that those that dried up spontaneously (and therefore had a shortened dry period between 23 and 31 d) had no difference in milk production compared with goats with the 56-d dry period. In sheep, a large-scale retrospective study has demonstrated that dry periods shorter than 30 d are detrimental to milk production in the next lactation (Hernandez et al, 2012). However, controlled work is required to disentangle the effects of dry period length from the variability in management practices common in a commercial setting.…”
Section: Dry Period Length and Omission: Effect On Milk Productionmentioning
confidence: 99%
“…Furthermore, although a substantive body of work is now available on the effects of dry period length on dairy cows, research is minimal in small ruminants. A 5-yr longitudinal examination of 6,762 lactations on one farm resulted in a broad recommendation of a 30-to 60-d dry period being appropriate for sheep (Hernandez et al, 2012). This dry period length was recommended based on milk yield and conception rate but did not consider effect on metabolic states.…”
Section: Dry Period Length and Omission: Effect On Negative Energy Bamentioning
confidence: 99%
“…Longer initial dry periods have been shown to reduce yield and length of subsequent lactation periods as well as leading to poor health in cows, Chilean sheep and Lacaune sheep (Natzke et al 1975;Pinedo et al 2011;Hernandez et al 2012). However, we did not observe such effects in the present study, suggesting that the positive effects of antibiotic dry therapy can outweigh the potential negative effects due to longer initial dry periods.…”
mentioning
confidence: 98%
“…In addition, previous studies of this therapy in dairy sheep have not examined in detail the various factors that may influence its success, such as dry period length, which can be crucial for subsequent milk yield (Hernandez et al 2012). These investigations are particularly important for optimising production while minimising antibiotic use.…”
mentioning
confidence: 99%